Student involved conferences - Stiggins, Rick; Assessment Training Institute (Portland, Oregon : Assessment Training Institute, 1999)
The practical conferencing formats and strategies for student self-evaluation offered in this training videos delivers a key motivational approach that works in helping students achieve
Title from cover
Presenter: Rick Stiggins
Keywords: Student participation in curriculum planning; Teacher participation in curriculum planning; Education, Secondary -- Curricula